Influence Of Promotion And Brand Image On Determining Society’s Interest To Request Classic Dangdut Songs At Radio Rama FM Bandung - Maya Dora, Yenny; Alawi, Anwar (International Journal of Psychosocial Rehabilitation, 2020)
Radio Rama FM Bandung is one of radio that broadcasts dangdut with various genres, ranging from classical dangdut, koplo, to EDM. In addition, Rama FM also often promotes by using various media both offline and online. The image of Rama FM itself among the society is considered good or positive, because Rama FM often holds various activities involving the society in it, and this radio is one of the dangdut radios that has been around for a long time. However, public interest in requesting classical dangdut songs is still small and is still dominated by Koplo dangdut. The purpose of this study is to determine the effect of promotions and imagery on people’s interest to request classical dangdut songs on Rama FM Bandung radio. Research data collection was carried out by distributing questionnaires to 122 respondents, namely the Rama FM radio listening society. The analytical method used in this research is descriptive and verification analysis. And the data obtained from the analysis using the SPSS program, Lisrel or path analysis to determine the direct relationship between variables in the study. The results of this study indicate that the promotion variable significantly influences interest, but the image variable has no significant effect. However, together the promotion and image variables influence the society’s interest to request classic dangdut songs on Rama FM Bandung radio.